Teaching-learning tendencies and strategies used in the leadership development of nurses - Cristiano Caveião; Aida Maris Peres; Ivete Palmira Sanson Zagonel; Simone Coelho Amestoy; Marineli Joaquim Meier
ABSTRACT Objective: To identify the tendencies and teaching-learning strategies used for leadership development in the discipline Nursing Administration in higher education institutions in Brazil. Method: Non-experimental, type survey, descriptive and exploratory, cross-sectional, with quantitative approach. Results: The dialogued lecture strategy was cited as used by 241 (91%) professors, followed by research, by 237 (89%), and discussion or group work, by 221 (83%). Strategies not used were: spiral learning, 166 (63%), and online programs, 151 (57%) professors. The strategy that presents higher tendency of use is that of online courses, 104 (39%). Conclusion: among the strategies mentioned, all are aligned with the directions given in the literature for nursing education, but these strategies and methodologies influence the formation of leader nurses differently.